Association between the APOB XbaI and EcoRI polymorphisms and lipids in Chinese: a meta-analysis - Gu, Wei (Lipids Health Dis, 2015)
BACKGROUND: No previous meta-analysis was to report the association between the apolipoprotein B (APOB) XbaI and EcoRI polymorphisms and serum lipids in Chinese. We performed the study to investigate their potentially association. METHODS AND RESULTS: Studies in English and Chinese were found via a systematic search of Pubmed, Embase, CNKI and Wanfang databases. The dominant genetic model and random-effects model were used to pool data from individual studies. As a result, a total of 30 articles with 5611 subjects for XbaI and 2653 subjects for EcoRI were included in the current study. For the XbaI polymorphism, overall, subjects carrying X+ allele were significantly associated with higher TC,TG and LDL compared with X-X- genotype (Pvalue =0.0006, OR (95 %) = -0.55 (-0.86,-0.23); Pvalue = 0.0004, OR (95 %) = -0.30 (-0.47,-0.14); (Pvalue = 0.05, OR (95 %) = -0.23(-0.46,-0.00), respectively). Similar results were observed in the subgroups of Han, healthy individuals (HT), coronary heart disease (CHD), cerebral infarction (CI), and cholelithiasis. For HDL, positive association between X+ allele with Lower lipid value was found in CHD and CI subgroups. For EcoRI polymorphism, overall, the E- allele carriers were found to be obviously linked with elevated LDL and lower HDL compared with E + E+ genotype (Pvalue = 0.02,OR (95 %) = -0.27 (-0.49,-0.05); Pvalue = 0.01, OR (95 %) = 0.17 (0.03, 0.30), respectively). TC was significantly high in subjects carrying E- allele in the subgroup of hyperlipidemia. No evidence of publication bias was observed. CONCLUSIONS: The two genetic variants of APOB may be associated with serum lipids in Chinese.